The Relationship Between Emotional Intelligence and Psychological Well-Being in Female Students at Islamic Boarding Schools in Padang City - Alfadillah Rehani Setalia; Roza Eva Susanti (Causalita, 2025)
This study aims to determine the relationship between emotional intelligence and psychological well-being among female students at the Islamic boarding school in Padang City. The research method used is a descriptive quantitative approach with Pearson correlation product moment analysis technique. The participants in this study amounted to 279 female students at the Madrasah Aliyah level. The instruments used include the Assessing Emotional Scale (AES) and Ryff’s Psychological Well-Being Scale. The results show that there is no significant relationship between emotional intelligence and psychological well-being (r = 0.026; p = 0.668 > 0.05). This finding indicates that emotional intelligence does not directly influence the psychological well-being of female students, suggesting that other factors such as social environment and academic pressure are more dominant.